Efeito da variação diária na temperatura corporal no incremento metabólico pós-prandial (SDA) da espécie Lithobates Catesbeianus - Lino, Noele Paschoini Leão (2019)
Introduction: The postprandial metabolic increment is characterized by a fast elevation in postprandial metabolic rate. The increase in O2 consumption continues until reaching a peak of consumption, that may occur days after the ingestion of the food, in species that ingested large volumes. After the peak, there is a decrease in the metabolic rate to a similar level to the standard (rest). The investigations regarding the mechanisms involved during the postprandial metabolic increment (SDA) of the Lithobates catesbeianus species were performed under a constant regime of body temperature. Such stability differs from what actually occurs with these animals that depend on the temperature of the environment to regulate their body temperature. Objective: To analyze the effects of body temperature on postprandial metabolic response (SDA) of the Lithobates catesbeianus species maintained at three temperature regimes: constant 20˚C, constant 25°C and oscillating with daily cycles of 25°C in the daytime period and 20°C in the nighttime period. Materials and methods: Twenty-one frogs of the species Lithobates catesbeianus (bullfrog) were used, with a mean body mass of 314 ± 10g. O2 consumption was used to determine the metabolic rate of the animals. The animals were allocated to three different groups (n = 7), two groups submitted to constant temperatures of 20°C and 25°C (T-20 and T-25, respectively), and the group submitted to oscillating temperature, 25°C in the daytime period and 20°C in the nighttime period (T-oscillating). The animals initiated the protocol in fasting and after for a period of 48 and 72 hours of collection of the resting metabolic rate they were fed the equivalent of 10% of their body mass and maintained in respirometry analysis until values were observed close to the baseline, individually. Results: The change in the temperature did not interfere in the metabolic rate of the T-20, T-25 and T-oscillating groups. These presented similar values of the metabolic resting rate, at each of the temperatures, the metabolic rate of the group maintained under T-oscillating, as expected, was bigger in the daytime (25˚C) than in the nighttime (20°C). The temperature affected the maximum value of the postprandial metabolic increment, so that the T-25 group had higher VO2 peak compared to T-20. The animals in the T-oscillating group showed an increased metabolic increase similar to that presented by T-25. The metabolic scope followed the same pattern. The time to reach peak of VO2 during SDA was similar between the experimental groups. The T-oscillating group showed lower values to coefficient compared to the 25°C group and higher when compared to the 20°C group. The T-oscillating group had a shorter SDA duration compared to T-25 and T-20. The energy cost of SDA in the T-25 group was higher than in the T-20 group, remaining high even with the temperature oscillation. Like this the protocol performed under oscillated temperature promoted a postprandial metabolic increment process (SDA) more efficient for being faster and with lowest coefficient.